Identification of New Biomarkers of Posturo-Locomotor Instability in a Rodent Model of Vestibular Pathology - Marouane, Emna; Rastoldo, Guillaume; El Mahmoudi, Nada; Péricat, David; Chabbert, Christian; Artzner, Vincent; Tighilet, Brahim (Frontiers in Neurology, 2020)
The vestibular system plays a crucial role in maintaining postural balance. Unilateral vestibular lesions result in a typical syndrome characterized by postural imbalance, altered locomotor patterns and gaze stabilization, as well as cognitive and neurovegetative disorders. One of the main difficulties encountered in the development of new anti-vertigo drugs is the lack of sensitivity in the evaluation of this syndrome. Qualitative assessments of vestibular syndrome have been developed, but methods of conducting quantitative evaluations are critically lacking. Recently, assessments with a dynamic weight-bearing device (DWB®, Bioseb) revealed postural alterations in rats subjected to unilateral vestibular neurectomy (UVN). Our team is evaluating a new version of this device capable of quantifying additional parameters of postural and locomotor equilibrium. The objective of this study was to use this device to assess these new posturo-locomotor parameters in a rat model of a vestibular pathology. The biomarkers measured by this device are as follows: the barycenter, the support surface and the weight distribution of the rats when they were moving or stationary. Before UVN, the rats showed a symmetric distribution of their weight along the lateral. In the acute phase after UVN on the left side, the rats distributed more weight on the right side than on the left side and then distributed more weight on the left side. These results corroborate those presented in our previous study. The support surface of the rats increased between 1 day and 30 days after UVN, and the barycenter distribution reflected the weight distribution. In addition, our results show smaller changes in the weight distributions when the animals are moving compared with when they are stationary in the acute phase after UVN. This study provides new information on the static and dynamic postural balance patterns observed after unilateral vestibular loss in rats. These data are relevant because they objectively quantify the posturo-locomotor component of vestibular syndrome as well as the compensatory strategies used after vestibular loss. These results may guide the development of rehabilitation protocols for vestibular patients and the validation of pharmacological compounds favouring the restoration of equilibrium.